Photoexcitations of many-electron atoms and ions by twisted light. (August 2015) - Fritzscheh, S; Seipt, D; Serbo, V; Surzhykov, A
Synopsis: The photoexcitation of (multi-electron) atoms and ions by twisted light has been explored within the framework of the density matrix theory and Dirac's relativistic equation. It is shown that the population of the excited atoms and, hence, their fluorescence emission are sensitive with regard to the transverse linear momentum and the (projection of the) total angular momentum of the incident light.